A aprendizagem de conhecimentos matemáticos em uma perspectiva interdisciplinar no projeto observatório da educação/CAPES/UEA - Costa, Yone Gama da (2013)
The research investigated the Mathematic`s apprenticeship in a public school of Manaus where is executed an interdisciplinary project of the Observatory of the Education/CAPES/UEA, especially at the 8 year of Elementary School, the read and write competence, from the application of a conjoint of strategies centralized in Math`s know-how in a interdisciplinary process with Portuguese capable of transcend the hampered of Math`s apprenticeship. The first chapter discussed the interdiscipline to search for aspects contained in the teacher knowledge and in the student knowledge acquired at the daily school. To deepen the proposed studies, has been opted for Fazenda (2008), Japiassu (2006), Gusdorf (1985) e Vasconcelos (2009). Also has been discussed the math`s knowledge, impulsed for the reflection of the own characteristics of the Math`s teach and, to help in these reflections, dialogued with Miorim (1998), Machado (2002) e Bürigo (1989). Advancing at the concept`s investigation, has been amplified the comprehension of mathematic knowledge through the read and write competence, directed for Perrenoud (1996), Terezinha Rios (2006), Marise Ramos (2006), Lerner (2002) e Ferreiro (2009). The second chapter runs over the methodological way centralized in a qualitative approach anchored by Demo (1997), Gamboa (2000), Zabala; Arnau (2010) and the reflections of the methodological procedures came through strategy of teach for Anastasiou (2012). At the end, the third chapter presents the verification and contradictions obtained through methodological delineation, calling attention to the necessity of adaptations during the daily activities. At the end of the research has been presented the final considerations and the possibilities of new questions and reflections. All this scenery reflects opportunities for discursions about the importance of problem-situation as didactic resource, as apprenticeship contexts much as school evaluation, and mainly as a new way to found the apprenticeship when we want to appreciate the development of competencies.